EFEKTIVITAS EKSTRAK DAUN KAWISTA (Limonia acidissima) TERHADAP SISTEM IMUN IKAN NILA (Oreochromis niloticus) YANG DIINJEKSI BAKTERI Aeromonas hydrophila - Febriana, Nurlita; Azhar, Fariq; Abidin, Zaenal; Setyowati, Dewi Nur’aeni (Jurnal Media Akuakultur Indonesia, 2024)
ABSTRACT Tilapia (Oreochromis niloticus) is a freshwater commodity that has high prospects in the fisheries sector. A. hydrophila bacteria is a pathogenic bacteria that can cause death, often found in freshwater fish. The kawista plant contains alkaloids, tannins, flavonoids, steroids and polyphenols. The objective of the study was to determine the effectiveness of kawista leaf extract Limonia acidissima) against the immune system of tilapia (Oreochromis niloticus) injected with A. hydrophila bacteria. This study was experimental using a completely randomized design (RAL) method consisting of 5 treatments with 3 replications namely K- (Not given kawista leaf extract and injected with 0.9% NaCl), K+ (Not given kawista leaf extract and injected with A. Hydrophila bacteria ), P1 (Addition of kawista leaf extract to feed with a dose of 0.5% and injection of A. hydrophila bacteria, P2 (Addition of kawista leaf extract to feed with a dose of 1% and injection of A. Hydrophila bacteria), P3 (Addition of kawista leaf extract to feed with dose of 2% and injection of A. Hydrophila bacteria).The results showed that giving kawista leaf extract with different doses affected the immune system in tilapia and fish survival.In this study the best treatment was obtained in treatment 2 with a total erythrocyte value of 1.92 x106 cell/mm3, total leukocytes 2.58x104 cell/mm3, differential leukocytes are divided into 4 parts, namely lymphocytes 66.7%, monocytes 5.33%, neutrophils 21.7%, and platelets 6.33%, hemoglobin 6.6%, hematocrit 17.33%, phagocytosis activity 69.93%, and a Total Bacteria Count (TBC) of OD620 3.53 and a survival rate of 68%. The conclusion was obtained that the use of kawista leaf extract at a dose of 1% in feed could improve the immune system of tilapia injected with A. hydrophila bacteria.